Identification of functionally important residues of the rat P2X4 receptor by alanine scanning mutagenesis of the dorsal fin and left flipper domains - Tvrdonova, Vendula; Rokic, Milos B; Stojilkovic, Stanko S; Zemkova, Hana (PloS one, 2014)
Crystallization of the zebrafish P2X4 receptor in both open and closed states revealed conformational differences in the ectodomain structures, including the dorsal fin and left flipper domains. Here, we focused on the role of these domains in receptor activation, responsiveness to orthosteric ATP analogue agonists, and desensitization. Alanine scanning mutagenesis of the R203-L214 (dorsal fin) and the D280-N293 (left flipper) sequences of the rat P2X4 receptor showed that ATP potency/efficacy was reduced in 15 out of 26 alanine mutants. The R203A, N204A, and N293A mutants were essentially non-functional, but receptor function was restored by ivermectin, an allosteric modulator. The I205A, T210A, L214A, P290A, G291A, and Y292A mutants exhibited significant changes in the responsiveness to orthosteric analog agonists 2-(methylthio)adenosine 5'-triphosphate, adenosine 5'-(γ-thio)triphosphate, 2'(3'-O-(4-benzoylbenzoyl)adenosine 5'-triphosphate, and α,β-methyleneadenosine 5'-triphosphate. In contrast, the responsiveness of L206A, N208A, D280A, T281A, R282A, and H286A mutants to analog agonists was comparable to that of the wild type receptor. Among these mutants, D280A, T281A, R282A, H286A, G291A, and Y292A also exhibited increased time-constant of the desensitizing current response. These experiments, together with homology modeling, indicate that residues located in the upper part of the dorsal fin and left flipper domains, relative to distance from the channel pore, contribute to the organization of the ATP binding pocket and to the initiation of signal transmission towards residues in the lower part of both domains. The R203 and N204 residues, deeply buried in the protein, may integrate the output signal from these two domains towards the gate. In addition, the left flipper residues predominantly account for the control of transition of channels from an open to a desensitized state.
Keywords: adenosintrifosfát; Rats; ivermektin; zvířata; Amino Acid Sequence; simulace molekulární dynamiky; Binding Sites; Alanine; terciární struktura proteinů; Mutagenesis; purinergní receptory P2X4; Humans; Ion Channel Gating; Protein Binding; HEK293 buňky; Protein Structure, Tertiary; Purinergic P2X Receptor Agonists; lidé; alanin; molekulární sekvence - údaje; gating iontového kanálu; metoda terčíkového zámku; Molecular Dynamics Simulation; Animals; HEK293 Cells; Patch-Clamp Techniques; Ivermectin; Molecular Sequence Data; sekvence aminokyselin; mutageneze; Sequence Alignment; vazebná místa; sekvenční seřazení; vazba proteinů; Receptors, Purinergic P2X4; krysa rodu Rattus; Adenosine Triphosphate; agonisté purinergního receptoru P2X